Assessing the effectiveness of the functional movement screen in predicting noncontact injury rates in soccer players - Smith, P. D.; Hanlon, D. (The Journal of Strength and Conditioning Research, 2017)
This study assessed if the Functional Movement Screen (FMS) can accurately predict noncontact injury in adult soccer players when normalizing noncontact injury occurrence against match exposure levels. Senior male players (n = 89) from 5 League of Ireland semiprofessional clubs participated in the study (mean age = 23.2 ± 4.4 years; mean height = 179.5 ± 6.6 cm; mean body mass = 77.5 ± 7.8 kg). Participants performed the FMS during preseason, and their injury occurrence rates and match minutes were tracked throughout 1 season. In total, 66 noncontact injuries were recorded. No significant difference was found in FMS composite scores between players receiving noncontact injuries and players not suffering a noncontact injury (p = 0.96). There was no significant difference in exposure-normalized noncontact injury incidence between those scoring 14 or below and those scoring above 14 on the FMS (0.36 vs. 0.29 non-contact injuries per player per 1,000 match minutes). Players scoring 14 or below on the FMS had an odds ratio of 0.63 (p = 0.45; 95% CI = 0.19-2.07) of receiving a noncontact injury. Despite previous research showing links between low FMS composite scores and subsequent injury, these results suggest that the FMS cannot accurately predict a male soccer player's likelihood of receiving a noncontact injury and that a lower FMS composite score does not significantly increase their noncontact injury incidence rate per 1,000 match minutes. Caution should therefore be used when using the FMS as a predictor of noncontact injury, and pain prevalence during the FMS, previous injuries, and training/match exposure levels should also be taken into account.